Expression of the cellular prion protein affects posttransfusion recovery and survival of red blood cells in mice. Issue 11 (30th May 2015) - Glier, Hana; Simak, Jan; Panigaj, Martin; Gelderman, Monique P.; Vostal, Jaroslav G.; Holada, Karel
Abstract : BACKGROUND: Cellular prion protein (PrP C ) is expressed on various cell types including red blood cells (RBCs). The PrP C plays a key role in the pathogenesis of prion diseases, but its physiologic function remains unclear. PrP C is expressed on CD34+ hematopoietic stem cells and its expression is regulated during blood cell differentiation including the erythroid line. STUDY DESIGN AND METHODS: We investigated the role of PrP C in RBC survival in circulation by transfusing a mix of biotin‐labeled RBCs from wild‐type (WT) and PrP knockout (KO) mice to groups of recipient mice (WT and KO). The proportion of biotinylated RBCs in peripheral blood was estimated by flow cytometry. RESULTS: KO RBCs displayed a markedly higher first‐day posttransfusion recovery but had a decreased survival in circulation when compared to WT RBCs. Similar results were obtained in all groups of transfused mice, irrespective of RBCs biotinylation level. In addition, we confirmed this finding in an analogous study using Tga20 mice overexpressing PrP C and KO mice of a different genetic background. CONCLUSION: Our results demonstrate that PrP C expression affects RBC recovery and survival in circulation.